Upaya Peningkatan Penggunaan Aplikasi Mobile JKN di Masyarakat Melalui Video - Nabilla Tri Pramita Utami; Muhlizardy Muhlizardy (FKIP, Universitas Palangka Raya, 2024)
Background; JKN Mobile is a non-face-to-face application that has many features and facilities participants in maximizing the national health insurance program organized by BPJS Health. In 2013, the number of JKN Mobile users in Surakarta reached 373.212 users. Providing information and understanding through video media to the public is a first step in increasing the use of JKN Mobile application. Objective; As a media of information and education to improve the use JKN Mobile applications in the community. Method; The method of this activity is implemented in the form of socialization through video media related to JKN Mobile. Result; Before the education related to the use of JKN Mobile application only 45% of population knew and used the application. After the education, 90% of the people who followed the activity knew and will use the JKN Mobile application to get health services. Conclusion; after educating through the video “ Let’s Use JKN Mobile: Online Health Services Solutions”, the public becomes aware of the use of JKN Mobile applications and will use them to access online health services.